A novel condominium management mode in Taiwan - Chin-Tai Kuo (Journal of Urban Management, 2020)
This study investigates a novel consultancy contract mode for condominium management in Taiwan by using transaction cost theory. This study finds that consultancy contracts offer property management companies lower personnel costs and a lower tax burden compared with full-responsibility contracts, and that such contracts are suitable for condominiums with minimal public funds, few households, and low management fees. However, under consultancy contracts, labor disputes are likely to occur; thus, distinguishing between powers and responsibilities and controlling service quality are difficult, and a property management company's corporate image is likely to sustain damage. Among the nine transaction costs, most of the respondents believe that transaction costs will decrease when using consultancy contracts, although for five transaction costs, some respondents felt that costs will increase, and for two items, no change is expected. This study provides six strategies for property management companies to select management modes and contracts: use a company website and advertising strategy, develop different service modules, use property service proposals, use management contract modes combined with new technologies, enhance the degree of authorization, and help protect employees' rights and interests.
Keywords: K11; K12; L10; M11; 710; Commissioned management committee; Condominium management mode; Consultancy contract; Full-responsibility contract; Property management companies; Transaction cost